A prospective study on gait-related intrinsic risk factors for lower leg overuse injuries. Issue 13 (18th February 2009) - Hesar, N Ghani Zadeh; Van Ginckel, A; Cools, A; Peersman, W; Roosen, P; De Clercq, D; Witvrouw, E
Abstract : Objective: To determine prospectively gait-related risk factors for lower leg overuse injury (LLOI). Design: A prospective cohort study. Setting: Male and female recruits from a start-to-run (STR) programme during a 10-week training period. Participants: 131 healthy subjects (20 men and 111 women), without a history of any lower leg complaint, participated in the study. Interventions: Before the start of the 10-week STR programme, plantar force measurements during running were performed. During STR, lower leg injuries were diagnosed and registered by a sports physician. Main Outcome Measures: Plantar force measurements during running were performed using a footscan pressure plate. Results: During the STR, 27 subjects (five men and 22 women) developed a LLOI. Logistic regression analysis revealed that subjects who developed a LLOI had a significantly more laterally directed force distribution at first metatarsal contact and forefoot flat, a more laterally directed force displacement in the forefoot contact phase, foot flat phase and at heel-off. These subjects also had a delayed change of the centre of force (COF) at forefoot flat, a higher force and loading underneath the lateral border of the foot, and a significantly higher directed force displacement of the COF at forefoot flat. Conclusions: These findings suggest that a less pronated heel strike and a more laterally directed roll-off can be considered as risk factors for LLOI. Clinically, the results of this study can be considered important in identifying individuals at risk of LLOI.